Wide-band metamaterial perfect absorber through double arrow shape printed on a thin dielectric - Siti Adlina Md Ali; Maisarah Abu; Siti Normi Zabri; Shipun Anuar Hamzah (Institute of Advanced Engineering and Science, 2021)
A wide-band metamaterial perfect absorber was introduced. The dual arrow shapes and the ground plane were in between the 0.0035λ TLY-3. Lump element technique was applied to enhance the absorption bandwidth, which was connected between both of the arrow structures. The limitation during fabrication process in using lump element, had seriously restricted its practical applications for microwave absorption. Then, a very thin line was connected between both arrow structures to represent the resistance by lump element which was expected to ease the fabrication process and practical applications as well. Four cases were analyzed: double arrow, double arrow with lump connected, double arrow with lump connected and 9 mm air gap, and thin line connected with 6 mm air gap. The fourth case achieved the highest operational absorbency frequency, which developed about 7.38 GHz (3.87 GHz to 11.25 GHz) approximately to 7.38 GHz. Three resonant frequencies were achieved; 4.17 GHz, 6.09 GHz and 10.30 GHz with perfect absorbency. These properties are expected to be used in practical applications such as satellite and radar communications transmission. These properties of the metamaterial absorber could increase the functionality of the metamaterial absorber to be used in any application especially in reducing radar cross section for stealth application.